Can adaptations of crop and soil management prevent yield losses during water scarcity? A modeling study - M. Heinz; M. Heinz; M. Heinz; M. E. Turek; M. E. Turek; B. Schaefli; B. Schaefli; A. Keiser; A. Holzkämper; A. Holzkämper (Hydrology and Earth System Sciences)
With climate change, the increasingly limited availability of irrigation water resources poses a major threat to agricultural production systems worldwide. This study explores climate adaptation options in soil and crop management to reduce yield losses due to water scarcity and irrigation restrictions during the 2022 summer drought. The focus is on potato production in the Broye catchment in Switzerland, which is representative of many mid-sized lowland catchments in central Europe facing reduced irrigation water availability. We employed the field-scale agro-hydrological Soil–Water–Atmosphere–Plant (SWAP) model in a distributed manner to simulate regional irrigation demand, yields, and deficits under drought stress. The results suggest that irrigation bans and drought in 2022 led to a 16.4 % reduction in potato yield due to a 59 % deficit in irrigation water. Our findings suggest that adding 1 % of soil organic carbon (SOC) down to a depth of 60 cm could have reduced the yield loss to only 7 %. Planting earlier-maturing potato varieties under less favorable pedoclimatic conditions further improves irrigation water productivity (IWP) and reduces irrigation water demand by 26 %. In this case, however, there is a tradeoff in yield, the reduction of which can only be −14.8 %. Overall, our findings highlight the great value of soil organic carbon for preventing productivity losses during droughts using the example of a recently experienced drought year. Furthermore, we show that irrigation water use efficiency can be optimized by location-specific combinations of adaptation choices. In the face of future droughts exacerbated by climate change, the measures studied here represent a valuable adaptation to mitigate yield losses and reduce dependence on irrigation.